PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP SRTES KERJA DAN PRESTASI KERJA KARYAWAN PADA PT. ACTS SURABAYA - Anjar Sulistyowati (J-MACC, 2019)
This study aims to examine and analyze the influence of leadership style and work environment on work performance and work performance of employees. This type of research is explanatory research and conducted at PT ACTS. The study population was employees of PT ACTS Surabaya, with a total sample of 90 people. The analysis technique used uses the smart partial least square (smartPLS) approach. The results of the study prove that leadership style has a negative and significant effect on work stress. The work environment has a positive and significant effect on work performance. Job stress has a negative and significant effect on the work performance of PT ACTS Surabaya.